T-radical and strongly T-radical supplemented modules - Koşar, B.; Nebiyev, C. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We define (strongly) t-radical supplemented modules and investigate some properties of these modules. These modules lie between strongly radical supplemented and strongly -radical supplemented modules. We also study the relationship between these modules and present examples separating strongly t-radical supplemented modules, supplemented modules, and strongly -radical supplemented modules.